The Relationship Between Peer Social Support and Academic Stress Among Students - Yunidar, Yunidar; Nirwana, Herman (The Future of Education Journal, 2026)
This study aims to describe: (1) the level of academic stress among students, (2) the level of peer social support, and (3) to test the significance of the relationship between peer social support and academic stress experienced by students. This research employs a quantitative method with a descriptive correlational research design. The population of this study consists of 421 students from SMPN 1 Kotanopan who were registered during the July-December semester of the 2025 academic year, with a sample of 241 students selected using Stratified Random Sampling. The instruments used were the "Peer Social Support Checklist" and the "Academic Stress Checklist." Data were analyzed using descriptive techniques and Pearson's Product Moment correlation. The results of the study indicate that (1) the peer social support for students at SMPN 1 Kotanopan is at a high level, (2) academic stress among students at SMPN 1 Kotanopan is at a low level, and (3) there is a significant negative relationship between peer social support and academic stress. This study indicates that when the level of peer social support is high, academic stress among students is low.